Adoption of Artificial Intelligence in Retail: Examining the Impact of Technological and Organizational Factors on Customer Retention and Loyalty - Ismoth Zerine; Younis Ali Biswas; Md Zulkernain Doha; Humayra Mehreen Meghla; Mohammad Rashed Hasan Polas (goodwood publishing, 2025)
Purpose: This study examines the factors influencing retail firms’ intentions to adopt Artificial Intelligence (AI) to enhance customer retention and loyalty in Dhaka, Bangladesh. It focuses on perceived usefulness, perceived ease of use, competitive pressure, Technological Readiness, and organizational innovativeness as key determinants of AI adoption. Research Methodology: A quantitative approach with a hypothetical-deductive design was applied. The study used a cross-sectional survey of 250 retail firms selected through stratified random sampling in Dhaka. Data were collected using structured questionnaires and analyzed using statistical techniques to evaluate relationships among variables. Results: The findings reveal that all five factors significantly and positively influence retail entrepreneurs’ intention to adopt AI. This indicates that both technological factors and organizational capabilities play essential roles in shaping AI adoption decisions within the retail sector. Conclusions: AI adoption can help retail businesses strengthen customer engagement, improve retention, and enhance competitiveness in Dhaka’s retail market. Limitations: This study is limited to Dhaka and uses a cross-sectional design, which may restrict generalizability and the ability to observe changes over time. Contribution: This study offers practical insights for retail managers by highlighting the importance of Technological Readinessand a culturee of innovationin thehadoptionoof f AI. It also contributes to the literature on AI adoption in emerging markets.